2009
DOI: 10.1590/s1413-70542009000300010
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência agronômica de superfosfato triplo e fosfato natural de Arad em cultivos sucessivos de soja e milho

Abstract: RESUMOConduziu-se este estudo, com o objetivo de avaliar os efeitos de doses de adubos fosfatados sobre a cultura da soja e do milho, em cultivos sucessivos. O experimento foi realizado em casa de vegetação da UFGD, em vasos contendo amostras de 5,5 dm 3 de um Latossolo Vermelho Distroférrico argiloso, sendo utilizado como fontes de fósforo (P) o superfosfato triplo (SFT) e o fosfato natural de Arad (FNA). O FNA foi utilizado sob duas formas. Em uma, considerou-se o P total (Arad T) e, em outra, apenas a fraçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 6 publications
2
8
0
12
Order By: Relevance
“…These characteristics of the soil cause imbalance in the dissolution reaction of natural phosphates, reducing the intensity in the release of P from this fertilizer to the soil (Ono et al, 2009;Fontoura et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics of the soil cause imbalance in the dissolution reaction of natural phosphates, reducing the intensity in the release of P from this fertilizer to the soil (Ono et al, 2009;Fontoura et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, scientific studies have demonstrated the agronomic and economic importance of using natural phosphates because they contribute to better P use by plants along the cultivation time (Ono et al, 2009;Souza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Médias acompanhadas pela mesma letra minúscula na coluna não se diferem pelo teste de Tukey a 5 %. & Smyth, 1999;Resende et al, 2006b;Costa et al, 2008;Guedes et al, 2009;Ono et al, 2009). O elevado teor de Ca trocável e a leve acidez do solo (Quadro 1) não impuseram grande restrição à solubilização dos fosfatos de rocha.…”
Section: Para Os Tratamentos Corrigidos Por Meio Dos Fosfatos De Rochunclassified
“…The lack of an effect on the maize (2011/12) yield from the anticipated TSP application may be assigned to the following: (i) the high solubility of this fertilizer and resulting immediate availability of P to the system, which favors greater absorption by forage plants and/or adsorption by soil colloids soon after its application (ONO et al, 2009); (ii) the lower DM yields and accumulations of P produced in this crop by the TSP compared with the MTP applications to the black oat (2011) crop preceding maize 2011/12 (Figure 3), resulting in a reduced P return to the system; and (iii) the lower effect of TSP than has been observed and proven in medium to long term studies (PROCHNOW et al, 2003;RESENDE et al, FRANZINI et al, 2009). …”
Section: Grain Yield and Phosphorus Accumulation And Export In Maize mentioning
confidence: 99%